Political Action of the Catholic Hierarchy and the Use of Religion in Political Organizations (Peru, 1920–2021): Evidence and Long-Term Analysis - Fernando Armas Asín (Religions, 2022)
This article presents the characteristics that the Catholic hierarchy has displayed over the course of a century in the political arena, as well as the importance that religious elements have exercised over the legitimacy of some parties and governments in Peru. It specifically analyzes the clergy and their relation with the State, as well as interpreting how they understood their participation and influence in local politics. In addition, parties and regimes over the course of a century are analyzed, emphasizing the presidential election campaigns of 1990 and 2021, in order to discuss the limits that political organizations have experienced in monopolizing religious representations. This study will help to better understand the nature of Catholicism in Latin American politics.